Screening of major hepatotoxic components of Tripterygium wilfordii based on hepatotoxic injury patterns - Meng Li; Qiong Luo; Xi Chen; Furong Qiu; Yanyan Tao; Xin Sun; Chenghai Liu (BMC, 2023)
Abstract Background Tripterygium wilfordii Hook. F. (TwHF), a traditional Chinese medicine, is widely used in the treatment of rheumatoid arthritis. Due to multiorgan toxicity, particularly hepatotoxicity, the application of TwHF is restricted. To clarify the hepatotoxic substances, zebrafish, hepatocytes and macrophages were used for screening based on hepatotoxic injury patterns. This study provides a basis for further elucidation of the hepatotoxic mechanism of TwHF. Methods First, 12 compounds were selected according to the chemical categories of TwHF. The fluorescence area and fluorescence intensity of zebrafish livers were observed and calculated. The viability of two hepatocyte lines was detected by CCK8 assay. TNF-α and IL-1β mRNA expression in bone marrow-derived macrophages was used to evaluate macrophage activation, a factor of potential indirect hepatotoxicity. Finally, the hepatotoxic characteristics of 4 representative components were verified in mice in vivo. Results Parthenolide, triptolide, triptonide, triptobenzene H, celastrol, demethylzeylasteral, wilforlide A, triptotriterpenic acid A and regelidine significantly reduced the fluorescence area and fluorescence intensity of zebrafish livers. The viability of L-02 or AML-12 cells was significantly inhibited by parthenolide, triptolide, triptonide, celastrol, demethylzeylasteral, and triptotriterpenic acid A. Parthenolide, triptolide, triptonide, celastrol, demethylzeylasteral and triptobenzene H significantly increased TNF-α and IL-1β mRNA levels in macrophages, while triptophenolide, hypodiolide and wilforine significantly reduced TNF-α and IL-1β mRNA levels. Triptotriterpenic acid A, celastrol and triptobenzene H at a dose of 10 mg/kg significantly increased the levels of mouse serum alanine aminotransferase and aspartate aminotransferase and aggravated liver inflammation. Conclusions Parthenolide, triptolide, triptonide, celastrol, demethylzeylasteral, triptotriterpenic acid A and triptobenzene H might be the main hepatotoxic components of TwFH. Among them, only triptotriterpenic acid A presents direct hepatotoxicity. Triptobenzene H exerts indirect liver damage by activating macrophages. Parthenolide, triptolide, triptonide, celastrol, and demethylzeylasteral can directly and indirectly cause liver injury.